The Effect of Simulation Education on Knowledge About Basic Life Support (BLS) Skills in the Amateur Football Player Community in Donoyudan Village - Argariswandha Nurvian; Ratih Dwilestari Puji Utami; Lalu Muhamad Panji Azali (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Basic Life Support (BLS) is the initial treatment for patients who experience cardiac arrest, respiratory arrest or airway obstruction. BLS includes several skills that can be taught to anyone, namely recognizing sudden cardiac arrest, activating the emergency response system, performing initial cardiopulmonary resuscitation (CPR) and how to use an automated external defibrillator (AED). The aim of the research was to analyze the effect of simulation education on knowledge about basic life support skills (BLS) in the amateur football player community in Donoyudan Village. This research was quasi-experimental research. The research design used was a one group pre-test-posttest pre-experiment design. The population was all amateur football players in Donoyudan Village totaling of 22 people using a total sampling technique and the instrument used was a questionnaire with the Wilcoxon test data analysis technique. The results showed that the majority of the adult category was 12 respondents (54.5%), the majority had a high school education as many as 20 respondents (90.9%), unemployed as many as 10 respondents (45.5%) and 10 respondents (45.5%) had sufficient knowledge before and had good knowledge about Basic Life Support (BLS) after. It can be concluded that there is an effect of simulation education on knowledge about basic life support skills (BLS) in the amateur football players community in Donoyudan Village with a p value of (0.000).